1867 Neb. Laws 68, An Act to Incorporate Nebraska City, § 25. - (:unkn) unknown (General Publisher, 1867)
The city council shall regulate the keeping and sale of gun-powder within the city[.]
--
Keywords: GUN POWDER STORAGE